Is diversity our strength? An analysis of the facts and fancies of diversity in Toronto - Ahmadi, Donya (A+BE | Architecture and the Built Environment, 2018)
A prominent characteristic of the city of Toronto is its increasing diversity, with half of the city’s population being foreign-born. While the concept of diversity appeals to Toronto’s reputation as a multi-cultural haven, the city’s approach to managing diversity is becoming increasingly instrumentalist, i.e. diversity is considered an asset as long as its benefits are economically valuable. As a result, inner-city neighbourhoods in Toronto are thriving due to development projects and services, while the most diverse neighbourhoods in the inner-suburbs are left in a dire state. This article presents an analysis of how the concept of diversity used within policy euphemises systemic discrimination and inequality based on race, class and gender. It serves to reveal the mismatch between policy rhetoric on diversity and its materialisation in the daily lives of the inhabitants of a low-income Toronto innersuburb, by juxtaposing policy discourses with inhabitants’ everyday experiences. By illustrating how inhabitants reproduce negative essentialised stereotypes based on diversity markers, the article argues that talking diversity as an alternative to or an escape from problematising the intertwined systems of race, class and gender oppression, could potentially serve to perpetuate them.